2013
DOI: 10.1080/17290376.2014.903620
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sexual behaviour and practice and HIV prevalence indicators among young people aged 15–24 years in Zambia: An in-depth analysis of the 2001–2002 and 2007 Zambia Demographic and Health Surveys

Abstract: HIV and AIDS still pose a major public health problem to most countries in sub-Saharan Africa, Zambia included. The objective of the paper is to determine changes in selected sexual behaviour and practice and HIV prevalence indicators between 2001–2002 and 2007. We used the Demographic and Health Survey Indicators Database for the computation of the selected indicators. We further used STATA 10.0 to compute significance tests to test for statistical difference in the indicators. The results indicate some chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The studies for adolescents and young men were more focused on the prevention of STIs and unwanted pregnancies in specific populations and circumstances, 16,17,29,30,32 and the results were more dependent on the characteristics of the participants in each study. Therefore, the factors identified are not generalizable to the wider population of young men.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies for adolescents and young men were more focused on the prevention of STIs and unwanted pregnancies in specific populations and circumstances, 16,17,29,30,32 and the results were more dependent on the characteristics of the participants in each study. Therefore, the factors identified are not generalizable to the wider population of young men.…”
Section: Discussionmentioning
confidence: 99%
“…Primary sexual abstinence in young men 11e14,16e20, 22,29e33,39e42 and middle-aged men ranged from 3.4% to 83.3% and 5.5%e32.8%, respectively. 11,39 Furthermore, the age categorization given in the selected studies showed that the prevalence for 10-to 19-year-old men was the highest (27.7%e 83.3%), 12,13,16,18,22,30,33,39 followed by 15-to 24-year-old men (3.4%e59.7%) 13,14,16,17,19,31,32,39,41 and 25-to 45-year-old men (5.5%e32.8%) 11,39 (Table 1). Table 1 shows that the overall prevalence of secondary abstinence reported in 22 studies ranged between 0% and 83.6% in men younger than 60 years ( Table 1).…”
Section: Primary Sexual Abstinencementioning
confidence: 99%
See 3 more Smart Citations